2018
DOI: 10.1016/j.cct.2018.08.002
|View full text |Cite
|
Sign up to set email alerts
|

Deception in clinical trials and its impact on recruitment and adherence of study participants

Abstract: Deceptive practices by participants in clinical research are prevalent. It has been shown that as high as 75% of participants withheld information to avoid exclusion from studies. Self-reported adherence has been found to be largely inaccurate. Overcoming deception is a critical issue, since the safety of study participants, the integrity of research data and research resources are at risk. In this review article, we examine deception from the perspective of investigators conducting clinical trials; we describ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 107 publications
0
18
0
Order By: Relevance
“…Prior studies have raised concern that payment may lead research participants to mislead investigators, but the studies are limited to identifying cases in the published literature, retrospective self-report, hypothetical projections of potential behavior, and nonrepresentative populations. For example, Lee et al 3 identified 103 instances of deception, including concealment, fabrication, drug holidays, and collusion, in 90 studies selected from a literature review of articles that included the terms deception , deceit , and subversive subjects , among others. Most of these instances of deception were incidentally detected, and the authors of the review article acknowledge that “few studies have investigated deceit in research participants, and fewer studies have examined deceit as a primary objective.” 3 (p154) Our study did both.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Prior studies have raised concern that payment may lead research participants to mislead investigators, but the studies are limited to identifying cases in the published literature, retrospective self-report, hypothetical projections of potential behavior, and nonrepresentative populations. For example, Lee et al 3 identified 103 instances of deception, including concealment, fabrication, drug holidays, and collusion, in 90 studies selected from a literature review of articles that included the terms deception , deceit , and subversive subjects , among others. Most of these instances of deception were incidentally detected, and the authors of the review article acknowledge that “few studies have investigated deceit in research participants, and fewer studies have examined deceit as a primary objective.” 3 (p154) Our study did both.…”
Section: Discussionmentioning
confidence: 99%
“…Instead, it is necessary to develop, test, and implement comprehensive alternative approaches to minimize the likelihood of participant deception. 3 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Numerous studies in addiction science and elsewhere have emphasized concerns related to deceptive responding by research participants while assessing study eligibility (1,4,33). Although objective biomarkers (e.g., breath alcohol readings, urinalysis) are gold standard for verifying substance use status, there are times when collecting these samples may not be ethically or practically feasible.…”
Section: Discussionmentioning
confidence: 99%
“…Another-if subtle-aspect of Vulnerability relates to a recent article reporting that as high as 75% of participants withheld information to avoid exclusion from studies [28]. This creates the specter of Vulnerability once a patient has been included in a clinical trial.…”
Section: Additional Observationsmentioning
confidence: 99%